MASCULINITY, SEXUALITY AND THE BODY OF MALE SOLDIERS - Mankayi, Nyameka (PINS-Psychology in Society, 2025)
Considering that social identities such as gender, culture, race, age and class play a major role in constructing masculinity, this paper looks at how these intersect with the body and what discourses of masculinity and sexualities are in evidence in this respect in the overtly masculinist context of the military. Drawing on data from a larger study exploring 14 military men’s narratives on their masculinity, sexuality, sexual relationships and HIV/AIDS, the findings illustrate how successful masculinity in the military context is played out through particular bodily performances, including being physically strong, proving one’s strength through high risk military activities, and through hypersexuality. There is evidence that the body and other bodily representations and accessories related to being in the military (uniform, weapons, etc.) is a key area in which masculine identity is performed by men in this institution. The suggestion is that male sexual practices cannot be tackled without examining the intersection of the body and masculine identity and in the military this means a particular focus on the way in which the body is centred in performances and representations of being both a military person and a man.